Net foreign assets and real exchange rates revisited - Bleaney, Michael; Tian, Mo (Oxford University Press, 2014)
Theory suggests a significant positive relationship in long-run equilibrium between the net foreign assets (NFA) of a country and its real exchange rate. Empirical tests have ignored two issues: the large variation in cross-country trade/GDP ratios, which is likely to induce substantial cross-country differences in coefficients when net foreign assets are scaled by GDP, and the reverse causality associated with valuation effects. A real exchange rate appreciation reduces the absolute value of NFA denominated in foreign currency relative to domestic GDP, because of the sizeable component of non-tradable goods in domestic GDP. This endogeneity biases the test results. New tests are implemented that address these issues. The valuation effect bias is found to be significant. The new tests nevertheless still support the existence of a long-run positive relationship between NFA and real exchange rates.